2020
DOI: 10.3389/fonc.2020.00774
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1-Dependent Regulation of Heparanase Affects Invasiveness, Stem Cell Properties, and Therapeutic Resistance of Caco2 Colon Cancer Cells

Abstract: The heparan sulfate proteoglycan Syndecan-1 binds cytokines, morphogens and extracellular matrix components, regulating cancer stem cell properties and invasiveness. Syndecan-1 is modulated by the heparan sulfate-degrading enzyme heparanase, but the underlying regulatory mechanisms are only poorly understood. In colon cancer pathogenesis, complex changes occur in the expression pattern of Syndecan-1 and heparanase during progression from well-differentiated to undifferentiated tumors. Loss of Syndecan-1 and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In the present study, colony and mammosphere formation – two important functional readouts of CSCs - were consistently upregulated in both model cell lines upon overexpression of both sulfotransferases, indicating a stemness-promoting function of these enzymes. At the molecular level, our data point at an upregulation of several components of the notch signaling pathway, which we previously linked to Sdc-1 function in breast and colon cancer ( Ibrahim et al, 2017 ; Katakam et al, 2020a ). For example, Sdc-1 expression in inflammatory breast cancer is correlated with CD44, Notch-1, and Notch-3 expression, and siRNA knockdown of Sdc-1 results in a weaker CSC phenotype and reduced expression of Notch-1-4 and Hey1 in inflammatory breast cancer cells ( Ibrahim et al, 2017 ).…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, colony and mammosphere formation – two important functional readouts of CSCs - were consistently upregulated in both model cell lines upon overexpression of both sulfotransferases, indicating a stemness-promoting function of these enzymes. At the molecular level, our data point at an upregulation of several components of the notch signaling pathway, which we previously linked to Sdc-1 function in breast and colon cancer ( Ibrahim et al, 2017 ; Katakam et al, 2020a ). For example, Sdc-1 expression in inflammatory breast cancer is correlated with CD44, Notch-1, and Notch-3 expression, and siRNA knockdown of Sdc-1 results in a weaker CSC phenotype and reduced expression of Notch-1-4 and Hey1 in inflammatory breast cancer cells ( Ibrahim et al, 2017 ).…”
Section: Discussionsupporting
confidence: 60%
“…Since we previously showed that heparan sulfate proteoglycans are capable of modulating breast and colon cancer stem cell properties, associated with therapeutic resistance [ 20 , 21 , 22 , 23 ], we evaluated the potential influence of SDC3 on the growth of three-dimensional spheroids as a readout of stem cell activity in a hanging drop assay [ 24 ]. Both SDC3-depleted and control siRNA-treated SKOV3 and CAOV3 cells formed dense spheroids after 4 days of culture that were surrounded by a margin of more loosely arranged cells ( Figure 2 A, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Gene silencing and overexpression in Caco-2 cells revealed that heparanase expression and activity were upregulated in syndecan-1-depleted cells likely due to upregulation of the transcription factor Egr1. 55 Syndecan-1 depletion also increased stemness and invasiveness of Caco-2 cells in heparanase-dependent manner. Upregulated expression of heparanase resulted in increased resistance to radiotherapy and chemotherapy.…”
Section: The Heparanase/shed Syndecan-1 Axis Regulates Cancer Progresmentioning
confidence: 91%